Harmonisasi dan Eksekutif Review dalam Pengawasan dan Pembatalan Peraturan Kepala Daerah di Indonesia - Desip Trinanda; Wiana Perista (AHKAM, 2026)
Institutional overlap and procedural inefficiency between the Ministry of Law and Human Rights and the Ministry of Home Affairs in the harmonization and supervision of regional regulations have implications for the emergence of legal uncertainty at the regional level. This study aims to analyze the juridical implications of the shift in authority over the harmonization of Draft Regional Head Regulations based on Law Number 13 of 2022, evaluate the dualism of executive regulatory review at the regional level, and formulate an ideal model of regulatory supervision within the framework of the Unitary State of the Republic of Indonesia. This study used a normative juridical approach with a conceptual design and a statutory approach. Primary and secondary legal materials were collected through a literature study of relevant legislation and court decisions, then analyzed qualitatively through systematic and teleological interpretation. The results show that although executive review of Regional Regulations has been conditionally invalidated by the Constitutional Court, executive review of Regional Head Regulations remains constitutional as a form of hierarchical supervision within the realm of state administration or bestuur. However, the harmonization process conducted by the Ministry of Law and Human Rights, which runs in parallel with evaluation by the Ministry of Home Affairs, creates procedural inefficiency and an anomaly of pseudo-harmonization, especially when drafts are unilaterally amended after the harmonization process. The conclusion of this study emphasizes the importance of a clear demarcation line between the harmonization of formal-legality aspects by the Ministry of Law and Human Rights and the evaluation of policy-substance aspects by the Ministry of Home Affairs to ensure legal certainty. The theoretical contribution of this study lies in strengthening the governance of central–regional relations, while its practical implications take the form of recommendations for a sequential collaboration framework and the development of a nationally integrated one-stop digital supervision portal.